Entrepreneurial psychosocial profile of university women in the State of Mexico, Mexico - Nava, Elizabeth Evangelista; Vilchis, Carlos Alberto Baltazar; Araiza, Jesús Cabral; Chimal, Eduardo Martínez (Brazilian Journal of Science, 2024)
The present empirical research is a descriptive and correlational study from the psychosocial perspective, the objective is to analyze the relationship between the intention to undertake and variables such as family with businesses, work intention, initial motivations, personality traits, individualistic, collectivist and mixed values, support for self-employment in the educational center, difficulty to create a company and pereception of the entrepreneur, to integrate an entrepreneurial psychosocial profile of university women from Higher Education Schools in the State of Mexico, Mexico. The sample under study was obtained with the participation of 297 women. Among the main findings is the existence of weak positive relationships in most of the variables studied about entrepreneurship. The risk-taking personality trait is less commonly observed. The most important human values observed are individualistic self-direction, collectivist benevolence, and universalism as mixed value, in this sense, entrepreneurship in commercial businesses and social entrepreneurship are alternatives for the intention of entrepreneurship in university women. Regarding the support from the Educational Center, the correlation was little or non-existent, however, recovering the importance of promoting visits to companies to receive advice or seminars, university women also state that self-employment is stimulated, but the knowledge offered has a low average trend. Another finding is perceived difficulties, which are external such as funding, grants, bureaucracy and advice. Finally, the perception of the entrepreneur is positive.